Current understanding of the role of high-density lipoproteins in atherosclerosis and senescence. (November 2005) - Nofer, Jerzy-Roch; Walter, Michael; Assmann, Gerd
Numerous epidemiologic and interventional studies revealed that high-density lipoprotein (HDL) is an important risk factor for coronary heart disease. There are several well documented HDL functions that may account for the antiatherogenic effects of this lipoprotein. The best recognized of these is the capacity of HDL to transport cholesterol from the periphery to the liver, and thereby prevent cholesterol deposition in the arterial wall. Further properties of HDL that may also be antiatherogenic include its potent anti oxidative and anti-inflammatory action. In addition, HDL seems to be involved in processes related to senescence at both the cellular and whole-organism level. Both protein components of HDL (such as apolipoprotein A-I) and its lipid components (such as,   lysosphingolipids) appear to mediate the antiatherogenic and anti-aging effects of HDL. The purpose of this review is to summarize the novel functions of HDL that may protect from atherosclerosis and senescence.